Fe(III) greatly promotes peroxymonosulfate activation by WS2 for efficient carbamazepine degradation and Escherichia coli disinfection - Luo, Hongwei; Liu, Chenyang; Cheng, Ying; Zeng, Yifeng; He, Dongqin; Pan, Xiangliang (The Science of the total environment, 2021)
The biggest problem with Fe/PMS (peroxymonosulfate) system is the slow generation rate of SO4− due to inefficient Fe3+/Fe2+ cycle and the low decomposition efficiency of PMS. Here, we report the Fe3+-enhanced decomposition of PMS by a two-dimensional transition metal dichalcogenide WS2 for pollutant degradation and E. coli disinfection. Experimental results showed that the removal rates of six representative pollutants were all above 90% under various pH conditions. Over a wide range of pH values (2–9), the removal rate of carbamazepine (CBZ) in PMS/WS2/Fe3+ system almost reached 100% within 10 min, and E. coli could be inactivated by 97.3% within 1 min. WS2 in the system accelerated the Fe3+/Fe2+ cycle and participated in the activation of PMS. Electron paramagnetic resonance (EPR) measurements and scavenging experiments demonstrated that the SO4− and HO radicals were the main active oxidative species. The degradation pathway of CBZ was revealed based on its intermediates as determined by liquid chromatograph-mass spectrometer (LC-MS). The presence of common anions such as Cl− and HCO3− in PMS/WS2/Fe3+ system noticeably affected the CBZ degradation. The characterization results verified the structural stability and the reusability of WS2. These research findings suggest that the combination of Fe3+ and WS2 is a promising method for PMS activation to remove organic pollutants and inactivate pathogenic bacteria during the process of wastewater treatment. [Display omitted] •PMS/WS2/Fe3+ system can efficiently degrade pollutants and inactivate E. coli.•The effective working pH of PMS/WS2/Fe3+ system was across a wide range of 2–9.•Reaction mechanisms and degradation pathway of carbamazepine were proposed.•Excellent oxidation stability of PMS/WS2/Fe3+ system was achieved.